2012
DOI: 10.1109/tap.2011.2173448
|View full text |Cite
|
Sign up to set email alerts
|

Empirical-Stochastic LMS-MIMO Channel Model Implementation and Validation

Abstract: Abstract-Land Mobile Satellite (LMS) networks, forming a key component of future mobile Internet and broadcasting, can benefit from Multiple-Input Multiple-Output (MIMO) techniques to improve spectral efficiency and outage. LMS-MIMO networks can be obtained using multiple satellites with single polarization antennas with spatial multiplex channel coding, or by a single satellite with dual polarization antennas providing polarization multiplex channel coding. In this paper, a guide is presented showing the step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The channel model that is considered here is an empirical stochastic model for LMS-MIMO [26]. This model has been validated and compared with the other existing models [27].…”
Section: Channel Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The channel model that is considered here is an empirical stochastic model for LMS-MIMO [26]. This model has been validated and compared with the other existing models [27].…”
Section: Channel Modelmentioning
confidence: 99%
“…This model has been validated and compared with the other existing models [27]. The stochastic properties of this model are derived from an S-band tree-lined road measurement campaign (suburban area) using dual circular polarizations at low elevations [26]. A four-state Markov model presented in Figure 5 later in this section is used to determine the present channel state using the probability transition matrix P presented in (2); the corresponding parameters of the current channel state are then used to compute large-scale fading (shadowing) matrix H large and small-scale fading (multipath) matrix H small that are summed together (in dB) to produce the channel matrix, H, in the following:…”
Section: Channel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic processes arise naturally in many applications [29][30][31][32][33][34]. In this work, we are concerned with multivariable stochastic processes that are measureable and accumulated at defined intervals over a period.…”
Section: Concept Of Concatenated Processmentioning
confidence: 99%
“…Among the various schemes (space, polarization or frequency diversity) polarization diversity offers good results within limited space and bandwidth. Although it has been applied mainly to linear polarization, recently it was demonstrated that circular polarization (CP) diversity also offers significantly greater channel capacity, especially for line-of-sight propagation [1]. This creates a need for simple and compact dual CP antennas, such as reported in this communication.…”
Section: Introductionmentioning
confidence: 99%